2013
DOI: 10.1002/jobm.201200351
|View full text |Cite
|
Sign up to set email alerts
|

Detection and distribution of putative virulence associated genes inAeromonasspecies from freshwater and wastewater treatment plant

Abstract: The detection of genes responsible for Aeromonas virulence is a vital tool in establishing the potential pathogenicity of the bacteria, as these virulence genes may act alone or in synergy in the establishment of infections. Freshwater and wastewater mixed liquor samples were collected from Kat river and Fort Beaufort wastewater treatment plant in the Eastern Cape Province of South Africa. Polymerase chain reaction was utilized for the amplification of the different genes coding for virulence. All virulence as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…In brief, raw water without chlorination from these sampling points, except for dams, is frequently consumed or contacted by people. Several studies have reported Aeromonas isolation from aquatic environments [4,24,25] but these contained little data on the proportion of various component species, and no other studies done in Japan with such data were found. Investigation of Aeromonas species in the environment revealed the proportion of the bacteria in environmental water, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, raw water without chlorination from these sampling points, except for dams, is frequently consumed or contacted by people. Several studies have reported Aeromonas isolation from aquatic environments [4,24,25] but these contained little data on the proportion of various component species, and no other studies done in Japan with such data were found. Investigation of Aeromonas species in the environment revealed the proportion of the bacteria in environmental water, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Motility and flagella play a vital role in adhesion, biofilm formation, and colonization of several pathogenic bacteria, such as Aeromonas hydrophila [52, 53]. Our previous study has shown that Aeromonas isolates from the studied microhabitat possess some virulent potential [31], and the ability of these virulent strains to form biofilm in aquatic environment may enhance an elevated waterborne dispersal capacity, an attribute that has been related to an elevated risk of bacterial transmission and infectivity [54]. Biofilm formation and development by microorganisms play a vital role in the pathogenesis of a disease; hence, the biofilm forming capability demonstrated in vitro by Aeromonas isolates from Tyume and Kat rivers further suggests enhanced pathogenic status of these isolates.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted following the method described elsewhere [30, 31]. Template DNA was stored at −20°C until it was ready for use.…”
Section: Methodsmentioning
confidence: 99%
“…A pesar de que esta enterotoxina es común en cepas clínicas de Aeromonas, estudios han mostrado que cepas ambientales también poseen dicho gen encontrándose en más del 80 % de las cepas, las cepas analizadas en este trabajo proceden Oreochromis spp. de agua dulce, en dicha fuente este gen suele ser más prevalente (Ottaviani et al, 2011;Igbinosa & Okoh, 2013; Abu-Elala, Abdelsalam, Marouf, & Setta, CUADRO 2 Genes de virulencia detectados en cepas de Aeromonas (Chopra & Houston, 1999). Las lipasas son consideradas de importancia para la nutrición bacteriana, además de actuar como factores de virulencia (Onuk et al, 2013) y participar en la patogénesis en A. salmonicida (Chacón, Figueras, Castro-Escarpulli, Soler, & Guarro, 2003).…”
Section: Discussionunclassified